2020
DOI: 10.1038/s41598-020-78497-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of IgE specific for galactose-α-1,3-galactose in predicting cetuximab induced hypersensitivity reaction: a systematic review and a diagnostic meta-analysis

Abstract: Recombinant monoclonal antibodies are used for treating various diseases, from asthma, rheumatoid arthritis, and inflammatory bowel disease to cancer. Although monoclonal antibodies are known to have fewer toxic reactions compared with the conventional cytotoxic antineoplastic drugs, the cases of severe systemic hypersensitivity reaction (HSR) should be acknowledged. Our aim was to assess the diagnostic accuracy of the anti-IgE for galactose-α-1,3-galactose in patients with HSRs to cetuximab. We searched in Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…According to Lungulescu et al, a total of six studies assessed the diagnostic accuracy of the anti-IgE for galactose-α-1,3-galactose in patients with HSRs to Cetuximab. The meta-analysis concluded that more studies are needed to establish a protocol necessary for the proper prediction and avoidance of HSR related to Cetuximab [32]. Hence, we consider that the theme of the paper is important and interesting, even though it might seem to be without great novelty.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…According to Lungulescu et al, a total of six studies assessed the diagnostic accuracy of the anti-IgE for galactose-α-1,3-galactose in patients with HSRs to Cetuximab. The meta-analysis concluded that more studies are needed to establish a protocol necessary for the proper prediction and avoidance of HSR related to Cetuximab [32]. Hence, we consider that the theme of the paper is important and interesting, even though it might seem to be without great novelty.…”
Section: Discussionmentioning
confidence: 96%
“…A classic mAbs adverse effect is the triggering of hypersensitivity reactions (HSR), which most commonly can occur with the first infusion. Numerous studies highlight the triggering of hypersensitivity reactions as being related to the pre-existence of specific IgE antibodies [32][33][34]. It is already known that some people are more likely to develop IgE antibodies against galactose-α-1,3-galactose after being naturally exposed to galactose-α-1,3-galactose.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with a meta-analysis performed to assess the diagnosis accuracy of anti-α-Gal IgE in predicting the risk of cetuximab immediate HSR. From a compilation of 6 studies, the authors reported a pooled sensitivity of 73% (95% CI 62–81%) and a pooled specificity of 88% (95% CI 79–94%) [ 13 ]. Two studies included in this meta-analysis used ImmunoCap o215.…”
Section: Discussionmentioning
confidence: 99%
“…In sensitized patients, immediate HSR can occur following the first cetuximab infusion, highlighting the importance of identifying high risk patients [ 11 , 12 ]. Thus, an anti-cetuximab IgE screening has been suggested as a reliable strategy to identify those patients [ 13 ]. Moreover, we have validated an ELISA method in a prospective multicenter study for the screening of patients at high risk of immediate HSR before cetuximab infusion [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, meta-analyses have shown an increased risk of acute infusion reactions with antibodies to infliximab [35,36]. With regard to other specific IgE-testing, anti-Galactose-α-1,3-galactose (alphagal) IgE testing may be helpful in predicting the risk of immediate reaction with first administration of cetuximab, demonstrating a pooled sensitivity of 73% (95% CI 62-81%) and specificity of 88% (95% CI 79-94%) in a recent metaanalysis [18,37,38]. The alpha-gal epitope has also been demonstrated on abatacept and infliximab; reactions to abatacept and infliximab have been reported in patients with alpha-gal syndrome, although evidence is limited to whether these were directly due to alpha-gal.…”
Section: In Vitro Testsmentioning
confidence: 99%